History of Design and Design Law An International and Interdisciplinary Perspective - Aso, Tsukasa; Rademacher, Christoph; Dobinson, Jonathan (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
For the first time, this book provides an up-to-date history of product design and product design law covering 17 countries - Japan, Korea, China, Singapore, the United Kingdom, Germany, France, Italy, the Nordic countries (Denmark, Finland, Iceland, Norway and Sweden), Russia, the United States, Brazil and Australia - selected for their innovative or influential approach to design or design protection. Each country is the subject of two chapters - one on the history of design and the other on the history of design law - authored by experts in design and intellectual property (IP) law. This unique interdisciplinary approach explains why and how various national design protection systems (that can include design, copyright, trade mark, competition and civil laws) developed, making it an ideal book for students, researchers and lawyers. The book also serves as an international survey of different national policy and legal responses to historical developments and specific design and legal issues allowing readers to consider their advantages and disadvantages - and so is also recommended for policy and law makers, as well as organizations that administer IP rights. Topics include the subject matter of design protection; procedural and substantive requirements; design registration; infringement; and the overlap of design rights and other IP rights. The chapters on design history provide further context to the historical development of these legal concepts by considering major design movements, key designers and iconic designs and the current state of design. The chapters highlight the connected and often complementary relationship between the two histories, not only for each country, but at the regional and international level, often as a result of government policies, trade, colonialism, immigration and globalisation. Design and design practice continue to become more global and evolve with developments in technology. At the same time, design laws are not internationally harmonized and continue to develop at the national level, with a number of significant changes occurring in recent years. This timely book shows how the lessons of the past continue to inform the future direction of design and the legal systems developed to protect it.
Asia:Japan -- History of Japanese Design -- History of Design Protection in Japan -- History and Current Status of Design in South Korea -- History of Design Protection in South Korea -- The Factors, Perplexity and Future of China's Design Development After the 'Reform and Opening Up' Policy -- History of Design Protection in China -- History and Current Status of Design in Singapore -- History of Design Protection in Singapore -- Europe:United Kingdom -- British Design -- History of Design Protection in the United Kingdom -- Design Made in Germany -- History of Design Protection in Germany -- History and Current Status of Design in France -- History and Current Status of Design Protection in France -- Italian Design -- History of Design Protection in Italy -- History and Current Status of Design in Scandinavia -- Design Protection in the Nordic Countries: The Past, the Present and Maybe the Future -- History of Design in Russia: 1917-2021 -- History of Design Protection in Russia -- North America: United States of America -- American Design, A Cultural History -- History of Design Protection in the United States of America -- Soth America:Brazil -- History and Current Status of Design in Brazil -- History and Current Status of Design Protection in Brazil -- Oceania:Australia -- A Chronological History of Australian Design -- A History of Australian Design Law -- Summary -- History of Design and Design Law: Connections, Influences and Observations.
Keywords: Information technology-Law and legislation; Mass media-Law and legislation; Industrial design; Design; Industrial Management; Civil law; Law-Philosophy.; Law-History.; IT Law, Media Law, Intellectual Property; Industrial Design; Design; Industrial Management; Civil Law; Theories of Law, Philosophy of Law, Legal History